Kemampuan Mahasiswa Pendidikan Bahasa Inggris dalam Menganalisis Kalimat Bahasa Inggris: English Education Students’ Ability in Analyzing English Sentences - Handoyo Puji Widodo (LP2M Universitas Islam Negeri Kiai Haji Achmad Siddiq Jember, 2004)
Teaching English grammar as a support for macro-skills remains a pedagogical priority in Indonesian higher education, yet students’ actual ability to analyze sentence structures is often underexamined. Drawing on theories of parts of speech, phrasal categories, and sentence elements, this study investigated second-semester English students’ proficiency in analyzing English sentences at Politeknik Negeri Jember. A case study design was employed, with 21 students analyzing six sentences (five simple, one complex) using the Chinese boxes method; data were analyzed using descriptive-qualitative methods. The findings revealed that although most students adequately identified basic parts of speech and sentence elements in simple sentences, significant difficulties emerged with conjunctions, noun phrases, verb phrases, prepositional phrases, complements, and modifiers, particularly in the complex sentence, where only 5% correctly identified subject, predicate, and object. The study concludes that sentence complexity inversely affects students’ analytical accuracy and recommends increased exposure to and explicit instruction in both lexical and functional grammatical elements, especially in complex sentence contexts. Pengajaran tata bahasa Inggris sebagai peran pendukung keterampilan berbahasa masih menjadi prioritas pedagogis di pendidikan tinggi Indonesia, namun kemampuan aktual mahasiswa dalam menganalisis struktur kalimat seringkali kurang diteliti. Berlandaskan teori kelas kata, kategori frasa, dan unsur kalimat, penelitian ini bertujuan untuk menginvestigasi kemampuan mahasiswa bahasa Inggris semester II dalam menganalisis kalimat bahasa Inggris di Politeknik Negeri Jember. Desain studi kasus digunakan, dengan 21 mahasiswa menganalisis enam kalimat (lima sederhana, satu kompleks) menggunakan metode kotak Cina; data dianalisis secara deskriptif-kualitatif. Temuan menunjukkan bahwa meskipun sebagian besar mahasiswa cukup mampu mengidentifikasi kelas kata dasar dan unsur kalimat pada kalimat sederhana, kesulitan signifikan muncul pada konjungsi, frasa nomina, frasa verba, frasa preposisi, pelengkap, dan keterangan, khususnya pada kalimat kompleks yang hanya 5% mengidentifikasi subjek, predikat, dan objek dengan benar. Penelitian menyimpulkan bahwa kompleksitas kalimat berbanding terbalik dengan akurasi analisis mahasiswa, serta merekomendasikan peningkatan eksposur dan pengajaran eksplisit unsur gramatikal leksikal maupun fungsional, terutama dalam konteks kalimat kompleks.